Treatment of Hormax Growth Regulating Substances on Early Germination and Growth of Sugarcane (Saccharum Officinarum L.) - Bambang Wicaksono Hariyadi; Nurul Huda; Dicki Wahyudi; Nurlina (Faculty of Agriculture, Merdeka University Surabaya, 2018)
The average production of sugar is 2.26 million tons per year, while consumption is about 5.10 million tons per year. This is what causes the number of production and consumption of sugar shows a fairly high gap. Extensification approach in increasing sugar cane production to achieve sugar self sufficiency target is quite difficult to achieve, so intensification program is one of the efforts that can be done through evaluation and optimization phase of germination and plant growth with application of growth regulator (Fitohormon). If this is done then to obtain a sugar cane plant that has the productivity and optimal yield is likely to be achieved (Ahmad Khuluq and Ruly Hamida, 2014). The experiment was conducted at Experimental Garden of Agriculture Faculty, Merdeka University, April-June 2017. Using Randomized Block Design with 3 replications. and 8 doses of Hormax growing growth regulator, among others: 0 ml/l water (Control); 1 ml/l water; 2 ml/l water; 3 ml/l water; 4 ml/l water; 5 ml/l water; 6 ml/l water; 7 ml/l water. In conclusion, the use of Hormax significantly affected the germination rate, the number of leaves, the number of roots, the wet weight and the dry weight per cane plant. Increased dose of Hormax followed by an increase in all variables of sugar cane observation. The highest results were shown dose of Hormax 7 ml/l water), but statistically not significantly different from the treatment dose of Hormax 6 ml/l water) and dose of Hormax 5 ml/l water. It is recommended that to assist the germination and early growth of sugar cane using a dose of Hormax 5 ml/l water.